High Temperature Corrosion of Aluminized AISI 4130 Steel with the Different Composition of NaCl/Na2SO4 Deposits - Badaruddin, Mohammad; Wang, Chaur Jeng; Saputra, Yudhistyra; Rivai, Abu Khalid (Makara Journal of Technology, 2015)
The high temperature corrosion of AISI 4130 steel can be increased by hot-dip aluminizing coating. The aluminized steel specimens with the deposit composition of 100/0, 30/70, 50/50, 70/30, and 0/100 (wt.%) NaCl/Na2SO4 were oxidized at 750 °C for 1-49 h periods. According to a parabolic rate constant (kp) value, the aluminized steel with deposit composition of 70/30 NaCl/Na2SO4 shows the highest kp value (3.71 × 10-11 g2cm- 4s-1), later followed by the kp value of 3.35 × 10-11 g2cm-4s-1 for 100/0 and the lowest kp value is 7.731 × 10-12 g2cm-4s-1 for 0/100. Whereas, the kp value for the aluminized steel without NaCl/Na2SO4 deposit is around 2.23 × 10-13 g2cm-4s-1. The presence of both salts and their mixtures destroyed protective Al2O3 layer on the aluminized steel, leading to the Fe2O3 growth locally. Whereas, the penetration of sulfur into the Al2O3 scale lead to the formation of Al2S3 and FeS in the aluminide coating. Therefore, the kinetics rate was increased. Furthermore, mixtures of 70 wt. % NaCl in Na2SO4 depositing on the aluminized steel produced the highest parabolic rate constant because the aluminide layer on the steel substrate experienced severe corrosion attack, leading to fail in formation of protective Al2O3 layer.